First observation of the decay $B^{+} → π^{+} μ^{+} μ^{-}$ - Collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2012)
A discovery of the rare decay $B^{+} → π^{+} μ^{+} μ^{-}$ is presented. This decay is observed for the first time, with 5.2 $σ$ significance. The observation is made using $pp$ collision data, corresponding to an integrated luminosity of 1.0 fb$^{-1}$, collected with the LHCb detector. The measured branching fraction is (2.3 $±$ 0.6 (stat.) $±$ 0.1 (syst.))$× 10^{-8}$, and the ratio of the $B^{+} → π^{+} μ^{+} μ^{-}$ and $B^{+} → \K^{+} μ^{+} μ^{-}$ branching fractions is measured to be 0.053 $±$ 0.014 (stat.) $±$ 0.001 (syst.).